Poguntano effect on cell viability in cholesteatoma keratinocyte of chronic suppurative otitis media - Harry A. Asroel; Aznan Lelo; Delfitri Munir; Jenny Bashiruddin; Restu Syamsul Hadi (Medicinski glasnik, 2020)
Aim: Chronic Suppurative Otitis Media (CSOM) with or without cholesteatoma is a global major problem and it is becoming a burden especially in developing countries. Studies have found that ethanol extracts of Puguntano leaves obtained by the percolation and socletation methods have phytochemical contents that provide anti-inflammatory effect. The aim of this study was to investigate the effects of ethanol extract and Puguntano on the viability of cholesteatoma keratinocytes. Methods: This in vitro experimental study included 8 groups of the cholesteatoma keratinocyte culture: not given puguntano leaf ethanol extract, three positive control groups given different concentrations of dexamethasone, and four groups that were given different concentrations of ethanol extract of leaf Puguntano. Results: A statistically significant decrease in procalcitonin level (p<0.001) and an amount of bacterial colonies (p<0.001) in four groups were found. Conclusion: This study showed that Puguntano leaf extract has the same effect as dexamethasone in terms of suppressing cell viability and has lower side effects compared to dexamethasone as other herbal medicines. Thus, the ethanol extract of Puguntano leaves can be used as an alternative for the prevention of cholesteatoma.
Keywords: inflammation; otitis; treatment